Pembuktian Penetapan Tersangka Dalam Persidangan Praperdilan - Steven Makaruku; Arter Lukas Tulia (Criminal of Law Department, Faculty of Law, Pattimura University, 2019)
The Criminal Procedure Code (KUHAP) is very different from Herziene Inlands Reglement (HIR), the Criminal Procedure Code adopts the principle of due process of law, which protects the rights of a suspect. Pretrial is an institution that oversees and can judge whether or not the act of determining the suspect conducted by the investigator is in accordance with the minimum principle of proof and in accordance with Article 183 and Article 184 paragraph (1) of the Criminal Procedure Code.